Efforts to Develop Children's Social-Emotional Skills at Bakti Kayu Kunyit Islamic Kindergarten - Aisa Dimilia; Repsi Dalyani; Nenni Surbayani; Elvi Susti; Ririn Fransiska (International Journal of Technology and Education Research, 2026)
This qualitative case study investigates the effectiveness of Islamic value-based interventions in developing social-emotional competencies among children aged 4–6 years at TK Islam Bakti Kayu Kunyit. Data were collected over three months through classroom observations, semi-structured interviews with teachers and parents, and analysis of behavioral documentation. Thematic analysis revealed significant improvements in children's emotional regulation (40–50% increase) and prosocial behaviors (104–219% increase). Daily Islamic routines, prophetic storytelling, and structured play-based activities provided a culturally resonant framework for scaffolding empathy, self-regulation, and conflict resolution. Teacher modeling and intentional emotional scaffolding emerged as pivotal mechanisms of change, while consistent parent-school collaboration further amplified positive outcomes. However, variability in pedagogical execution and moderate family engagement highlighted challenges related to teacher training and structural support. The study demonstrates that integrating Islamic moral education with evidence-based social-emotional learning strategies effectively addresses developmental gaps in early childhood. These findings offer a replicable, faith-integrated pedagogical model for educators seeking to nurture both psychological well-being and character formation during the critical golden period, while emphasizing the need for sustained professional development and flexible family partnership frameworks to optimize implementation.